Shakespeare & creative criticism - Conkie, Rob; Maisano, Scott (Shakespeare &, 2019)
"What kinds of critical insights are made possible only or especially via creative strategies? This volume examines how creative modes of writing might facilitate or inform new ways to critically engage with Shakespeare. Creative writing, demonstrated in a series of essays, reflections, stories and scenes, operates as a vehicle for exploring and articulating critical and theoretical ideas. In doing so, Shakespeare's enduring creative and critical appeal is newly understood and critiqued"--